THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT BPR KARTASURA MAKMUR - Nugroho, Andrian Wahyu; Wagiyem, Wagiyem (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The research team behind this project hopes to learn how factors like workplace discipline and employee motivation affect productivity. What we have here is an example of associative study. A multiple regression test was used to assess the hypothesis. Saturated samples are utilized in the sampling process. All 45 employees falling within the purview of BPR Kartasura Makmur make up the sample for this study. The SPSS program, version 26, is utilized for data processing. Multiple linear regression, classical assumption testing, hypothesis testing, and determination coefficient testing were all part of the data analysis approach. There was a nialiR square (R2) of 0.799 in the determination test, according to the data presented in the prior chapter. You may use this figure to evaluate how the work environment, discipline, and motivation all play a role in employee performance. This number indicates that 80% of an employee's performance is affected by their work environment, work discipline, and work incentive all at once. Other variables impact the remaining 20%. Employee performance at BPR Kartasura Makmur is positively and significantly impacted by work discipline and motivation, according to the premise of work environment factors. According to the results, work discipline is the single most important factor affecting employee performance. Keywords: work environment, work discipline, work motivation, employee performance